Minerals and the Developing Economies (fafba686-ef20-48a4-ae2a-b2a91cf994fa) - Charles J. Johnson; William S. Pintz; William A. Vogely (Society for Mining, Metallurgy & Exploration, 1985)
This chapter on the role of minerals in developing economies is oriented toward economic policy issues. The discussion and analysis cut across the technical, economic, legal, and policy fields. The goal of this chapter is to pro- vide relevant background information important to individuals involved with the minerals sector in developing countries. Where possible, trends are shown to provide a basis for understanding the evolving role of minerals in developing economies. This chapter is divided into the following five sections: (1) characteristics of developing countries (which presents selected statistical comparisons); (2) government objectives in developing countries; (3) government policy formulation in developing countries; (4) determinants of future trends, and (5) a summary of the chapter's major points combined with the authors' view. CHARACTERISTICS OF DEVELOPING COUNTRIES There are 155 nations in the world categorized as "developing countries." In total these nations represent about one third of the value of the world's mineral production, three quarters of the world's population, and over half of the world's land surface area. The group of so-called developing countries is quite diverse and there are exceptions to almost any general observation about the group as a whole. Most definitions of the term "developing country" are based on levels of per capita income. However, if per capita income is the sole criterion used in categorization, then several oil-exporting countries would jump from the category of developing country to the category of developed country.a Obviously, this results in a poor fit with respect to other measures. In general, the majority of developing countries can be characterized by relatively low per capita income, high population growth rates, high levels of unemployment, low levels of education, short average life ex- pectancies, income distribution skewed toward the highest 20% of the population, and a large share of exports represented by primary commodities. b For the purposes of this chapter a slightly modified version of the widely used World Bank system of classification (shown in Table 1.2.1) is used. As summarized in Table 1.2.1, developing countries are divided into three main groups based on estimated gross national product (GNP) per capita. It should be noted that the high- income, oil-exporting countries have characteristics of both developing and industrialized countries; however they are included for most statistical comparisons within the group of developing countries. Of the 155 developing countries in the world, approximately half produce minerals other than common building materials, and only 32 account for more than five percent of world pro-